Treatment for neovascular age-related macular degeneration: reasonable expectations of physicians and patients - A.B. Durasov (РМЖ "Клиническая офтальмология")
A.B. Durasov Ophthalmology Clinic "Octopus" ("Tochka zreniya" Ltd), Samara, Russian Federation Neovascular age-related macular degeneration (nAMD) is a progressive chronic multifactorial disease requiring long-term, lifelong anti-VEGF therapy. Treatment outcomes are not always in line with the results of randomized clinical trials and do not meet the expectations for therapy whose success is assessed differently by patients and physicians. Good functional and anatomical results are expected from antivasoproliferative therapy under certain conditions, e.g., accurate evaluation of some patient characteristics (baseline visual acuity, type of choroidal neovascularization, comorbidities, status of retinal fluid and its differentiation), timely (as early as possible) treatment initiation after verifying diagnosis, and strict adherence to a proactive personalized "Treat-and-Extend" (T&E) regimen that implies a required number of injections with individual intervals. Poor adherence to treatment (non-compliance or nonpersistence of anti-VEGF therapy) significantly affects treatment outcomes in real-world clinical practice. This paper reviews criteria which predict the response to antivasoproliferative therapy and improving treatment adherence. The authors describe four fundamental principles to be met by an ideal regimen of anti-VEGF therapy for nAMD. Keywords: neovascular age-related macular degeneration, nAMD, "Treat-and-Extend", T&E, adherence, nonpersistence, anti-VEGF. For citation: Durasov A.B. Treatment for neovascular age-related macular degeneration: reasonable expectations of physicians and patients. Russian Journal of Clinical Ophthalmology. 2021;21(3):169–174 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-169-174.